Cross-sectional analysis of clinical aspects in patients with long-COVID and post-COVID syndrome - Schulze, Hannah; Charles James, Jeyanthan; Trampe, Nadine; Richter, Daniel; Pakeerathan, Thivya; Siems, Nadine; Ayzenberg, Ilya; Gold, Ralf; Faissner, Simon (Frontiers in Neurology, 2022)
Objective The post-COVID syndrome is incompletely understood regarding pathophysiology, clinical aspects, patients at risk and diagnostic tools to stratify patients for therapeutic approaches. Here, we set out to assess sociodemographic and clinical aspects in patients with long-COVID and post-COVID syndrome. Methods We performed a cross-sectional analysis of patients having presented at our specialized University hospital outpatient clinic. Patients were assessed regarding clinical presentation, fatigue, symptoms of depression and anxiety and impairment of smell. Results A total of 101 patients were included (73.3% female). 78.2% had a mild course of COVID-19. At presentation, 93.1% suffered from fatigue, 82.2% from impaired concentration and 79.2% from impaired memory, 53.5% had impaired sleep. The most common secondary diagnosis found in our cohort was thyroid disease. Analysis of fatigue showed that 81.3% of female patients and 58.8% of male patients had severe combined fatigue. Female gender was an independent risk factor for severe fatigue (severe cognitive fatigue OR=8.045, p=0.010; severe motor fatigue OR=7.698, p=0.013). Males suffered from more depressive symptoms which correlated positively with duration from symptom onset. 70.3% of patients with anamnestic impairment of smell had a hyposmia, 18.9% were anosmic. Interpretation Most long-COVID patients suffered from severe fatigue with female sex as independent risk factor. Fatigue was not associated with symptoms of depression or anxiety. Patients with long-COVID symptoms should receive an interdisciplinary diagnostic and therapeutic approach depending on the clinical presentation.